Mixed Martial Art (MMA) Tasikmalaya as a Medium for Islamic Character Education A Da'wah Strategy for the Globalized Generation Z - Muhammad Shaff Ribbel (LPPM Institut Pendidikan Nusantara Global, 2026)
This study explores how Mixed Martial Arts (MMA), developed within religious communities in Tasikmalaya, serves as a medium for Islamic character education and an effective da'wah strategy for Generation Z. Through an experiential learning approach, participants not only train physically but also internalize Islamic values such as patience, discipline, humility, and emotional control. MMA helps build an active, modern, and competitive Muslim identity. Social media functions as a reflective and expressive platform where Islamic values are creatively conveyed to resonate with younger audiences. Da'wah strategies involving role models, community engagement, visual storytelling, and digital platforms have proven effective in fostering spiritual awareness and social connection. The findings show that MMA transforms participants from mere athletes into Muslims with strong character, strengthening grounded and impactful da'wah practices relevant to the challenges of globalization.